GAMMA-GLUTAMYL TRANSFERASE (GGT) BLOOD TEST - Karabayeva Lola Xudayberdiyevna; Davirova Gulbaxor Mamasaliyevna (Web of Journals Publishing, 2026)
The gamma-glutamyl transferase (GGT) test is a test used by blood test providers to diagnose or rule out liver and bile duct diseases. It measures levels of GGT, an enzyme found primarily in your liver that helps protect your cells from damage. Alcohol, drugs, and diseases that affect your liver, pancreas, or heart can cause high GGT levels.
Keywords: Gamma-glutamyl transferase, liver, bile ducts, ALP tests, enzyme.